Range extension and molecular confirmation of the critically endangered and endemic catfish Hemibagrus punctatus (Jerdon, 1849) (Siluriformes: Bagridae) from the southern Western Ghats - P, Bhavadharani; M. S. , Sowmiya; Sajan , John; Rajendran, Kumar; K. Kannan (Indian Journal of Fisheries, 2025)
Hemibagrus punctatus (Jerdon, 1849) is endemic to the Western Ghats and native to the Cauvery River system. The species faces distributional uncertainty due to misidentifications and the lack of voucher specimens. This study confirms the range extension of H. punctatus from the Cauvery River tributary, Bhavani River to the Bharathappuzha River in Kerala. Samples were collected from both rivers, with larger number of samples collected from the Bhavani River (n=230). The analysis revealed subtle morphometric variations between the two populations in head length (21.2-27.3% vs 24.7-26.4% in SL), dorsal to adipose distance (16.5-21.2% vs 13.7-16.5% in SL) and eye diameter (12.6-17.8% vs 10.3-16.9% in HL). Species confirmation was done using the mitochondrial DNA (mtDNA) Cytochrome Oxidase I (COI) gene sequencing, and taxonomic position was compared with known Hemibagrus species. Genetic analysis revealed that Hemibagrus punctatus differs from its sister taxon H. menoda with a divergence of 4.4% and other Hemibagrus species with 12.5-19.8% in partial mitochondrial COI gene sequences.  Keywords: Bharathappuzha, Critically Endangered, Hemibagrus punctatus, Molecular confirmation, New range